2020
DOI: 10.1101/2020.08.26.267831
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 genomic and quasispecies analyses in cancer patients reveal relaxed intrahost virus evolution

Abstract: Numerous factors have been identified to influence susceptibility to SARS-CoV-2 infection and disease severity. Cancer patients are more prone to clinically evolve to more severe COVID-19 conditions, but the determinants of such a more severe outcome remain largely unknown. We have determined the full-length SARS-CoV-2 genomic sequences of cancer patients and healthcare workers (HCW; non-cancer controls) by deep sequencing and investigated the within-host viral quasispecies of each infection, quantifying intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
2
10
0
Order By: Relevance
“…Detecting and locating genomic positions of low-frequency variants from culture-derived specimens can provide insight into the reliability of intrahost single nucleotide variants (iSNVs) called from clinical specimens. The role of intrahost genomic variability in SARS-CoV-2 may be important in inferring transmission events ( 39 ) and may be responsible for significant complications in patients with malignancies ( 40 , 41 ). Thus, such low-frequency variants require ongoing detection and surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Detecting and locating genomic positions of low-frequency variants from culture-derived specimens can provide insight into the reliability of intrahost single nucleotide variants (iSNVs) called from clinical specimens. The role of intrahost genomic variability in SARS-CoV-2 may be important in inferring transmission events ( 39 ) and may be responsible for significant complications in patients with malignancies ( 40 , 41 ). Thus, such low-frequency variants require ongoing detection and surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, diversity remains low and viral evolution is mainly shaped by purifying selection ( Abu-Raddad et al, 2020 ; Valesano et al, 2021 ; Popa et al, 2020 ; Tonkin-Hill et al, 2020 ; Lythgoe et al, 2021 ). Nonetheless, variability in the number of detectable viral variants was observed among patients with short-term infections ( Popa et al, 2020 ), and still limited data indicate that SARS-CoV-2 intra-host diversity might increase with age ( Al Khatib et al, 2020 ) and in cancer patients ( Al Khatib et al, 2020 ; Siqueira et al, 2020 ). Intense monitoring of viruses transmitted by these (and other) patient categories will thus be required to assess whether they can transmit genetically diverse viral genomes.…”
Section: Sars-cov-2 Genetic Diversitymentioning
confidence: 99%
“…Indeed, several studies have already revealed the existence of large numbers of withinhost viral populations in SARS-CoV-2 (Wolfel et al, 2020, Shen et al, 2020, Lythgoe et al, 2020, Butler et al, 2020). Genomic and quasispecies analyses showed large numbers intra-host nonsynonymous mutations in nasopharyngeal and oropharyngeal swabs of SARS-CoV-2 positive cases (Zhou et al, 2020a, Siqueira et al, 2020). Intrahost single nucleotide variants (iSNVs) were were also observed in bronchoal-veolar lavage fluid samples of of 8 SARS-CoV-2 patients(Shen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%